INNOVATION OF LOCAL GOVERMENT BLANG DHOD VILLAGE, TANGSE, PIDIE - Cut Zamharira; Cut Zamharira (Jurnal Geuthèë: Penelitian Multidisiplin, 2018)
The existence of an area, including the village, can be judged by whether there is a change in a better direction. For this reason, the skills of the village apparatus and the involvement of local residents are needed to make it happen. Change can be seen from the emergence of innovation in the environment. Innovation is an absolute necessity for answering the agenda of bureaucratic reform. This paper aims to examine the form of innovation that was driven in Blang Dhod village, Tangse sub-district, Pidie District since 2015. This study uses a descriptive qualitative method, through the process of collecting data from interviews with informants from government officials and villagers at the location, research, observation, and documentation. The results of the study revealed that there were four new types of programs developed in the village, namely coffee processing as a superior product of Blang Dhod village, Amil Zakat, Infaq, and Sadaqah (BAZIS), blood bank, and online village magazine (village website).  Keywords: innovation, local geverment, Blang Dhod village.